The Effect of Positive Working Conditions on Work Engagement and Teaching Classroom Practices: A Large Cross-Sectional Study in Switzerland - Addimando, Loredana (Frontiers in Psychology, 2019)
Introduction. Teaching methods and techniques represent important classroom practices that promote both academic achievement and the efficacy of learning processes: the use of a complex array of teaching practices by educators in the classrooms has been frequently associated with better student academic outcomes (Hattie, 2012; 2009). So far, less is known about the psychological aspects linked to the working endeavors able to promote the adoption of different teaching techniques in educational contexts. The research. The present cross-sectional quantitative research aimed at estimating the cumulative network of associations between psychological resources at work (e.g., social support, sense of autonomy, job satisfaction) and both work engagement and the use of teaching classroom practices. Sample and method: The sample was composed of in-service teachers (N=1,370) recruited in primary and lower secondary public schools in urban and suburban areas of Canton Ticino (Switzerland). Self-administered quantitative measures were used to evaluate the following constructs: social support, job satisfaction, teachers’ autonomy, work engagement, and teaching classroom practices. The data were analyzed using structural equation modeling with decomposition analysis of total effects in direct and indirect effects. Results. The hypothesized structural model reported a good fit with the empirical data (NC = 2.7; RMSEA= .051, NFI = .951, NNFI = .950, CFI = .968) and support the interpretation of the structural model. The main results revealed a large positive association between psychological resources at work and teaching classroom practices (β=.37). The level of work engagement seemed to be a minor element in promoting the use of teaching classroom practices (β=.10). Discussion. Overall, the results provide a fresh piece of evidence for the association between working conditions and teaching practices. In fact, teachers who perceive a supportive and satisfying working environment (both in terms of internal and external resources) are more likely to be engaged in their activities, and this in turn leads to a more heterogeneous array of teaching practices with students. The practical implications in terms of professional training and on-field intervention are discussed.